PENGARUH MODEL FUN LEARNING DENGAN SUPER MEMORI TERHADAP HASIL BELAJAR SISWA KELAS IX MATA PELAJARAN AL-QUR’AN HADITS DI MTS MAMBA’UL HUDA KRASAK TEGALSARI - Ahmad Izza Muttaqin; Muhammad Endy Fadlullah; Putri Soviyatu Rohma (Tarbiyatuna Kajian Pendidikan Islam, 2021)
This research is an experimental research using pretest posttest control group design. By the population at the same time became the sample in the tryed, I used of two classes, IX.3 and IX.5, each is there are 24 students. The results of this study indicate student learning outcomes of class IX at MTs Mamba'ul Huda before an application of the learning model’s (pretest) have an average of 49.38 in this case it is in the low category. With the frequency of students who completed as many just 9 students with 37.5% percentage and the frequency of students who did not complete was 15 students with 62.5% percentage. While, after the implementation of the learning model’s (posttest) had an average of 80.0 in this case it was in the good category. With the frequency of students who completed was 19 students with 79.2% and the frequency of students who did not complete was 5 people with 20.8% percentage. Based on these results, it can be concluded from the application of the model’s fun learning with super memory has an effect on student learning outcomes at MTs Mamba'ul Huda in the school year 2020/2021.